Relieve Fatigue by Socializing in Sidoarjo City Park - Normalita, Ivanda (TEMALI : Jurnal Pembangunan Sosial, 2023)
City parks are one of the green open public spaces. The development of city parks gives meaning to the community because city people who are busy working very rarely interact. The existence of a city park as a public space provides movement for the community to be able to interact with other individuals. In Sidoarjo, there is a City Park called Abhirama Park. The Park is strategically located with easy access. This research aims to analyze the development of city parks as a space for interaction in the Sidoarjo community. The research results are regarding the situation of the Sidoarjo city park, as for the views of the people of Sidoarjo regarding the existence of parks and the various functions of city parks. The method used is qualitative, with data collection through interviews, observation, and documentation. This study uses the theory of Herbert Mead regarding symbolic interaction.